Bone Healing in Extraction Sockets Covered With Collagen Membrane Alone or Associated With Porcine-Derived Bone Graft: a Comparative Histological and Histomorphometric Analysis - Renzo Guarnieri; Luca Testarelli; Luigi Stefanelli; Francesca De Angelis; Francesca Mencio; Giorgio Pompa; Stefano Di Carlo (Stilus Optimus, 2017)
Objectives: The present paper reports data of a randomized study aimed to analyse and compare the histologic and histomorphometric aspects of bone healing in extraction sites covered with collagen membrane alone or associated with porcine-derived bone graft. Material and Methods: Thirty patients, with single extraction sockets without severe bone wall defects in the premolar/molar region, were included. Ten extraction sockets were grafted with porcine-derived bone and covered with collagen membrane (group 1), 10 sites were covered with collagen membrane alone (group 2), and 10 sites healed spontaneously (group 3). After 4 months of healing, 26 (8 in group 1, 9 in group 2, and 9 in group 3) bone core specimens were harvested for histologic evaluation, then dental implants were placed. Results: Sites in the group 1 and in the group 2 showed similar histologic and histomorphometric results without significantly differences in the percentage of vital bone (57.43% [SD 4.8] vs. 60.01% [SD 3.2]), and non-mineralized connective tissue 22.99% (SD 5.3) vs. 18.53% (SD 6.2). In group 1 a 16.57% (SD 3.8) of residual material was found. Conclusions: Results showed that the use of collagen membrane alone or associated to porcine-derived bone improves the healing bone process compared to that of extraction sites spontaneously healed. Moreover, histomorphometric data related to bone quality, indicated that extraction sites without severe walls defects and with a vestibular bone thickness > 1.5 mm, treated with a low resorbtion rate collagen membrane alone, do not need more than 4 months for dental implant insertion.